Minimizing the number of collectors to measure uniformity from center pivot systems - Pragada, Siva Ramakrishna (Kansas State University, 2008)
This report presents the methods to determine the minimum number of collectors to accurately measure the coefficient of uniformity and the average depth of applied water from fixed plate and moving plate center pivot sprinkler irrigation systems. This research conducted an uniformity analysis and an average depth analysis. In the uniformity analysis, catch can collected data from center pivot system tests were divided into base sets of 60 data points. Each base set was further divided into subsets of 30 data points each. T-tests were used to compare the CU values from the base data sets with CU values from each of the subsets. In the average depth analysis, center pivot system catch can data were divided into base sets with 20 data points. Each base data set was divided into 19 subsets. The 1st subset was generated by removing an exterior data point from the base set which was identified by number 1. The 2nd subset was generated by removing other exterior data point (identified by number 20) from the previously generated subset (1st subset). In this manner, a total of 19 subsets for each base set were generated by removing an exterior point from each previous subset. The percent difference (change) in average depth of each subset from the value of the average depth of the base set was calculated. The percent difference in average depth was then plotted against the associated number of collectors. Both analyses documented that a decrease in the number of collectors from the original density of collectors is acceptable to determine the uniformity and averaged depth of applied water from center pivot spans. Results from the uniformity analysis demonstrated that 20 collectors were as effective as 60 collectors to quantify the uniformity of a system. The depth analysis showed that 9 to 12 collectors may be needed to measure the average depth of a system (or a portion of a system) to within 5% to 7.5% of the true value.
Keywords: center pivot systems; center pivot collectors; minimum number of collectors; center pivot uniformity; fixed plate sprinklers; moving plate sprinklers; Agriculture, Agronomy (0285); Engineering, Agricultural (0539); Engineering, Environmental (0775)